Evaluation of the impact of genetic polymorphisms in glutathione-related genes on the association between methylmercury or n-3 polyunsaturated long chain fatty acids and risk of myocardial infarction: a case-control study - Norberg Margareta; Lundh Thomas; Jansson Jan-Håkan; Hallmans Göran; Bergdahl Ingvar A; Strömberg Ulf; Wennberg Maria; Engström Karin S; Rentschler Gerda; Vessby Bengt; Skerfving Staffan; Broberg Karin (Environmental Health, 2011)
Abstract Background The n-3 polyunsaturated fatty acids eicosapentaenoic acid and docosahexaenoic acid, which are present in fish, are protective against myocardial infarction. However, fish also contains methylmercury, which influences the risk of myocardial infarction, possibly by generating oxidative stress. Methylmercury is metabolized by conjugation to glutathione, which facilitates elimination. Glutathione is also an antioxidant. Individuals with certain polymorphisms in glutathione-related genes may tolerate higher exposures to methylmercury, due to faster metabolism and elimination and/or better glutathione-associated antioxidative capacity. They would thus benefit more from the protective agents in fish, such as eicosapentaenoic+docosahexaenoic acid and selenium. The objective for this study was to elucidate whether genetic polymorphisms in glutathione-related genes modify the association between eicosapentaenoic+docosahexaenoic acid or methylmercury and risk of first ever myocardial infarction. Methods Polymorphisms in glutathione-synthesizing (glutamyl-cysteine ligase catalytic subunit, GCLC and glutamyl-cysteine ligase modifier subunit, GCLM ) or glutathione-conjugating (glutathione S-transferase P, GSTP1 ) genes were genotyped in 1027 individuals from northern Sweden (458 cases of first-ever myocardial infarction and 569 matched controls). The impact of these polymorphisms on the association between erythrocyte-mercury (proxy for methylmercury) and risk of myocardial infarction, as well as between plasma eicosapentaenoic+docosahexaenoic acid and risk of myocardial infarction, was evaluated by conditional logistic regression. The effect of erythrocyte-selenium on risk of myocardial infarction was also taken into consideration. Results There were no strong genetic modifying effects on the association between plasma eicosapentaenoic+docosahexaenoic acid or erythrocyte-mercury and risk of myocardial infarction risk. When eicosapentaenoic+docosahexaenoic acid or erythrocyte-mercury were divided into ...